A Study of Kinesics Category and the Manifestation Towards a Toddler Attitudes - Laily Nur Affini (Universitas PGRI Semarang, 2017)
Kinesics, or body language, is one of the most powerful ways that humans can communicate nonverbally. It is used to portray moods and emotions and to emphasize or contradict what is being said. From the kinesics point of view, there are several facial expressions and gestures done to express respond, and do activities toward people around. From the research finding, there are kinesics expressions done from the child. There are several classifications in kinesics; Emblems a substitute for words and phrases. Illustrators go with or reinforce verbal messages. Affect Displays Show emotion. Regulators Control the flow and pace of communication. Adaptors Release physical or emotional tension. This study investigates on how a kid expresses their non-verbal behavior using the kinesics classification and based on them, the kid’s verbal expressions belong to illustrators, affect displays and adaptor.